2015
DOI: 10.1089/thy.2014.0603
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil Cytoplasmic Antibody–Positive Small-Vessel Vasculitis Associated with Antithyroid Drug Therapy: How Significant Is the Clinical Problem?

Abstract: ANCA screening is not systematically recommended for individuals on ATD therapy, particularly given the decreasing use of PTU in favor of TMZ/MMI. Particular attention should be given to the pediatric population with Graves' disease who receive ATD, as well as patients treated with thiouracil derivatives and those on long-term ATD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 55 publications
1
33
0
4
Order By: Relevance
“…They include drug-induced hepatitis, and the production of cytoplasmic anti-neutrophil antibodies (ANCA). ANCA-positive vasculitis occurs only in exceptional cases, and susceptibility to this condition seems to be higher in patients of Asian origin (26). The risk appears to increase with the duration of PTU therapy, following the opposite pattern to other adverse effects of ATDs, which typically occur during the first 3-6 months of treatment (25,26,27).…”
Section: Monitoring Atd Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…They include drug-induced hepatitis, and the production of cytoplasmic anti-neutrophil antibodies (ANCA). ANCA-positive vasculitis occurs only in exceptional cases, and susceptibility to this condition seems to be higher in patients of Asian origin (26). The risk appears to increase with the duration of PTU therapy, following the opposite pattern to other adverse effects of ATDs, which typically occur during the first 3-6 months of treatment (25,26,27).…”
Section: Monitoring Atd Treatmentmentioning
confidence: 99%
“…ANCA-positive vasculitis occurs only in exceptional cases, and susceptibility to this condition seems to be higher in patients of Asian origin (26). The risk appears to increase with the duration of PTU therapy, following the opposite pattern to other adverse effects of ATDs, which typically occur during the first 3-6 months of treatment (25,26,27). In adults, MMI/CMZ use has also been shown to be associated with ANCA positivity, although the risk for this combination is lower than that reported for PTU (26,28).…”
Section: Monitoring Atd Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that AAV can be induced by various drugs, for example by the thyroid drug propylthiouracil (PTU). Over 20% of patients with Graves' disease treated with PTU develop MPO-ANCA and some of them also an AAV-like disease (Wada et al 2002, Balavoine et al 2015.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%